Invariant algebras and geometric reasoning - Li, Hongbo (World Scientific, 2008)
The demand for more reliable geometric computing in robotics, computer vision and graphics has revitalized many venerable algebraic subjects in mathematics - among them, Grassmann-Cayley algebra and geometric algebra. Nowadays, they are used as powerful languages for projective, Euclidean and other classical geometries. This book contains the author's most recent, original development of Grassmann-Cayley algebra and geometric algebra and their applications in automated reasoning of classical geometries. It includes three advanced invariant algebras - Cayley bracket algebra, conformal geometric algebra, and null bracket algebra - for highly efficient geometric computing. They form the theory of advanced invariants, and capture the intrinsic beauty of geometric languages and geometric computing. Apart from their applications in discrete and computational geometry, the new languages are currently being used in computer vision, graphics and robotics by many researchers worldwide.